L'interloquée ; Les oubliées de l'oubli ; [et] Dé/générée - Causse, Michèle (Trois, 1991)
« L’androlecte est en effet un soliloque. C’est la production mentale, disons la pathologie langagière, de l’Andros qui, victime d’une faille principielle, n’a pas su, pas pu, pas voulu accéder au chiffre deux et qui, s’étant érigé en seul locuteur, n’a pas eu d’autre interlocuteur que lui-même. Avant même de parler, une femme en "Androlecte est inter-loquée". Soit au sens propre "interdite-interrompue". Le dictionnaire – depôt sacré des mots de l’androlecte – ne donne-t-il pas comme exemple cette phrase, ô combien illuminante: "Faute d’interlocuteur, elle se parlait à elle-même". (Petit Robert, Léon Bloy). Bécassine ayant cru sans doute dans le langage comme communication. » p.15 éditions Trois, 1990
Keywords: approches et analyses; arts; discipline; hétérosexisme; lesbianisme; sexisme; systèmes d'oppressions; études littéraires

Odd girls and twilight lovers: A history of lesbian life in twentieth-century America - Faderman, Lillian (Between men-between women, 1991)
Comme l'écrit Lillian Faderman, il n'y a « pas de constante en matière de lesbiennes », si ce n'est que les lesbiennes préfèrent les femmes. Dans ce livre révolutionnaire, elle récupère l’histoire de la vie lesbienne dans l’Amérique du XXe siècle, retraçant l’évolution de l’identité et des sous-cultures lesbiennes depuis les premiers réseaux jusqu’aux modes de vie divers plus récents. Elle puise dans des journaux, des manuscrits inédits, des chansons, des comptes rendus médiatiques, des romans, de la littérature médicale, des artefacts de la culture pop et des histoires orales de lesbiennes de tous âges et de tous horizons, découvrant un récit d'une profondeur et d'une originalité hors du commun.
Keywords: 1900-1999; amériques; approches et analyses; histoire et politique; lesbianisme; personnes lesbiennes; périodes historiques; régions géographiques; thématiques; états-unis

A lure of knowledge: Lesbian sexuality and theory - Roof, Judith (Between men-between women, 1991)
Lesbianism in literature has been dealt with rather indirectly in the past. Editors have led readers to the "artistry" of a work containing lesbianism, emphasizing instead the literary history and historical context of the work rather than the representations of lesbianism. The editor for Colette's The Pure and the Impure, for instance, affirms that Colette has a knowledge of a "strange sisterhood," but assures readers she has never strayed from the "normal." In the groundbreaking A Lure of Knowledge, Judith Roof demonstrates that representations of lesbian sexuality occupy specific locations or positions in the arguments, subject matter, and rhetoric of Western European and American literary criticism. She examines the political context of representations: how lesbian sexuality is used as a signifier an why it appears when and where it does. Roof argues that attempts to depict or explain lesbian sexuality spur anxieties about knowledge and identity. In reaction to and denial of these anxieties, lesbian sexuality is represented in film, literature, theory, and criticism as foreplay, as simulated heterosexuality, as erotic excess, as joking inauthenticity, as artful compromise, or as masculine mask in a specific repertoire of neutralization and evasion. Challenging the heterosexism of film theory and feminist theory, this book analyzes the rhetorical use of lesbian sexuality. Roof explores a range of discourses, from the woks of such authors as Anais Nin, Olga Broumas, Julia Kristeva, Jane Rule, Luce Iriguray, and Sigmund Freud, to films such as Emmanuelle, Desert Hearts, Entre Nous, and I've Heard the Mermaids Singing, to professional tennis.
Keywords: approches et analyses; arts; cinéma; communication; discipline; hétérosexisme; lesbianisme; personnes lesbiennes; sexualité; sexualité lesbienne; systèmes d'oppressions; thématiques; études culturelles; études littéraires